Evaluation of the Safety and Anti-cholangiocarcinoma Efficacy of CMC-Formulated Atractylodes lancea Rhizome Extract in Animal Models - Plengsuriyakarn, Tullayakorn; Na-Bangchang, Kesara (Pharmaceutical Science: New Insights and Developments Vol. 1, 2024)
Background: Cholangiocarcinoma (CCA) is commonly reported in Asia, with the highest incidence in northeastern Thailand. The lack of effective chemotherapeutic drugs has limited the chemotherapy of CCA. Previous in vitro and in vivo studies support further research and development of Atractylodes lancea (Thunb.) DC. (AL) as a potential candidate for treating CCA as a crude ethanolic extract. Aim: In the present study, we evaluated the toxicity and anti-CCA activity of the CMC (Chemistry, Manufacturing, and Control) capsule formulation of the ethanolic rhizome extract of AL (CMC-AL) in animals. Methods: This experimental, preclinical study focused on a pharmacological agent's safety (toxicity) and efficacy in animal models. The study included toxicity testing (to assess the formulation's safety) and anticancer efficacy testing (to evaluate its therapeutic potential). Major steps included acute, subchronic and chronic toxicity testing in Wistar rats and anti-CCA activity in a CCA-xenografted nude mouse model. According to the OECD guideline, the safety of CMC-AL was determined based on the maximum tolerated dose (MTD) and no-observed-adverse-effect level (NOAEL). The anti-CCA activity of CMC-AL in nude mice was evaluated after transplantation of CL-6 cells to evaluate inhibitory effects on tumor size progression and metastasis and survival time prolongation. Safety assessments included hematology, biochemistry parameters and histopathological examination. Lung metastasis was investigated using a VEGF ELISA kit. Results: Preclinical toxicity testing (acute, subchronic, and chronic) is essential to confirm the safety of the finished products, either chemicals or herbal products. All evaluations confirmed satisfactory pharmaceutical properties of oral formulation and safety profile of the CMC-AL with no overt toxicity up to the MTD and NOAEL of 5,000 and 3,000 mg/kg body weight, respectively. CMC-AL exhibited potent anti-CCA efficacy concerning inhibitory activity on tumor progression and lung metastasis. Conclusions: CMC-AL is safe and should be further investigated in a clinical trial as a potential therapy for CCA patients. The findings confirmed the safety profile of the CMC formulation of the standardized AL extract following a prolonged period of 365 days.